THE EUROPEAN CONGRESS OF RHEUMATOLOGY (PARIS, 11–14 JUNE 2014): PROBLEMS OF RHEUMATOID ARTHRITIS - A. S. Avdeeva; D. E. Karateev; L. N. Denisov; E. L. Nasonov (Научно-практическая ревматология, 2014)
The 15th annual European Congress of Rheumatology took place in Paris in June 2014. Its program was extremely diverse and included a discussion of new data pertinent to the diagnosis and treatment of the most common rheumatic diseases and problems of their etiology and pathogenesis, personified therapy, and many others. The Congress focused on the problems of early rheumatoid arthritis (RA). A number of papers concerned the efficiency and safety of different therapy regimens for RA at its onset, the discontinuation of biological therapy after achievement of remission, and the maintenance of drug-free RA remission. The Congress discussed new results of the tREACH trial comparing three treatment regimens for early inflammatory arthritis: combined therapy with methotrexate (MT), sulfasalazine, and hydroxychloroquine in conjunction with intramuscular glucocorticoids (GC); combined therapy with these drugs in conjunction with oral GC; and MT monotherapy with oral GC. A large number of reports dealt with the use of tumor necrosis factor-α inhibitors, the evaluation of their immunogenicity, and theanalysis of reasons for therapy discontinuation and adverse reactions. Some aspects of therapy with disease-difying antirheumatic drugs were discussed. A number of reports concerned the application of novel laboratory biomarkers for RA.Thus, sufficiently many new data that will be able to optimize therapy for common rheumatic disease, such as RA, were presented at the Congress.